NUMERICAL AND EXPERIMENTAL INVESTIGATIONS OF TRANSIENT CAVITATING PIPE FLOW - Bergant, Anton; Karadžić, Uroš (Journal of Energy Technology, 2024)
This paper investigates the effects of transient vaporous cavitation caused by the closure of the downstream end ball valve against the discharge. Numerical results are compared with the results of measurements in the simple reservoir-pipeline-valve apparatus. Pressures measured at the end points and at two equidistant positions along the pipeline are compared with computational results as piezometric heads. Comparisons between the results of two distinct water column separation tests and numerical simulations using an advanced discrete gas cavity model show good agreement. Two distinct column separation runs include active and passive column separation cases.